GAMBARAN PENGETAHUAN HIGIENE DAN SANITASI PENJAMAH MAKANAN DI PONDOK PESANTREN - Nasution, Andreanda; Septiana, Henni Rizki; Putri, Pramita Ariawati (Poltekkes Kemenkes Bandung, 2023)
Large-scale food processing in Islamic boarding schools has the potential to be carried out unhygienically and can cause disease. So it is important to know the hygiene knowledge of food handlers in Islamic boarding schools. This research aimed to describe the hygiene and sanitation knowledge of food handlers at the Darul Fallah Agricultural Islamic Boarding School. The research was conducted in February 2023 using interview guides, observation guides, field notebooks and cameras. Primary data was obtained through a questionnaire interview with 15 questions. Data analysis was done based on the scoring system and data presentation was done in the form of data tabulation.The Darul Fallah Bogor Islamic Boarding School manages the provision of food independently, including purchasing, cleaning, storing, processing, maintaining kitchen cleanliness and serving. Food is served buffet style, and leftovers are taken home. The interviews showed that three respondents knew about diseases transmitted through food, while one respondent only knew about diarrhea. In conclusion, school hygiene and sanitation knowledge is generally sufficient, with little knowledge of human and food factors. The food handlers at the Darul Fallah Agricultural Islamic Boarding School have sufficient knowledge of hygiene and sanitation, including clean uniforms, clean hair, nails, hands, and the prohibition of smoking. However, they lack knowledge about food and place factors, such as proper serving and storage temperatures as well as kitchen and canteen facilities.